The Effect of Zeitgeber (Fasting and Exercise) on Phase Advance Blood Glucose Circadian Rhythms in Endurance Athletes - Boukelia, Boukhemis; Sabba, Abdelhakim; Fogarty, Mark (International Journal of Sport Studies for Health, 2018)
Objectives: Fasting is usually associated with changes in the metabolic, psychological and physiological responses of athletes; advancing and/or delaying their biological clock and therefore, affecting their sport performance. The aim of this study was to assess the effect of Ramadan fasting on blood glucose level, mean arterial pressure (MAP), heart rate (HR) and skin temperature in 11 experienced endurance athletes.Methods: The study was conducted during the third and fourth weeks of Ramadan (26 May - 24 June 2017). Eleven northwest African male endurance runners volunteered to participate in this study (mean ± SD: Age 32 ± 8 years, mass 64 ± 5 kg, and height 1.72 ± 0.05 cm). All participants regularly trained between 18:00 - 19:00; aiming to complete their training close to the time of breaking of fast to allow for rapid rehydration and avoiding any health complications. Blood finger-pricking, blood pressure (BP), HR and skin temperature samples were taken every 2 hours over a 24-hour period during the 3rd or 4th weeks of Ramadan. Data were analysed using a two-way repeated measures ANOVA with Bonferroni-adjusted post hoc tests.Results: A clear within-day variation was revealed in blood glucose concentrations and HR (P < 0.05). Blood glucose concentration variation was directly associated with exercise and food intake but significant peaks were also observed prior to breaking fast. These peaks corresponded to the start of athlete’s usual daily routine and suggest the athletes were able to phase advance blood glucose circadian rhythms.Conclusions: The data presented demonstrates the combination of exercise and fasting phase shifted and adjusted the blood glucose concentration to start rising prior to training session.